Hubungan Umur Ibu, Paritas dan Penolong Persalinan dengan Kematian Neonatal di Wilayah Kerja Puskesmas Kabupaten Banjarnegara tahun 2013 - Isnaeni Rofiqoch; Jusuf S. Effendi; Dinan S. Bratakoesoema (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: The neonatal mortality rate is Banjarnegara district is high compared with a target of IMR in Central Java province. In 2012 the neonatal mortality rate in Banjarnegara reached 316 cases, whereas in 2013 there were 115 cases in all health centers working area. The high neonatal mortality rate in Banjarnegara influenced by the persistence of early marriage in woman, birth attendant by non skilled health worker (dukun bayi) and women’s parity more than 4.Objective: The purpose of this study is to analyze the correlation between maternal age, parity and birth attendants with the incidence of neonatal mortality and examine the most dominant factors influencing the incidence neonatal mortality in the Health Center working area in Banjarnegara.Method: This study is a case control study design with retrospective approach. The data consists of perinatal verbal autopsy and medical records as many as 136 respondents consisting of 68 mothers who gave birth to her child and neonatal death and 68 maternal and child alive. Subjects were mothers who gave birth a baby who died aged 0-28 days.Result and Discussion: Statistical analysis using Chi Square, Mann Whitney, and multiple logistic regression. The results showed maternal age and parity variables were not significantly corerelated with neonatal mortality (p> 0.05), the variables significantly corerelated with neonatal mortality was birth attendants with p = 0.001. The results of logistic regression showed the strength of the corerelation from the most dominant variable to the smallest variable were birth attendants with OR: 5.64 (95% CI: 1.81 to 17.4), maternal age OR 3.97 (CI 95%, from 1.54 to 10.22), and parity OR: 0.32 (CI 95% 0.12 to 0.87).Conclusion: In conclusion, there was no relationship between maternal age and parity with neonatal mortality but there was a relationship between birth attendants with neonatal mortality. Based on the results of the multivariable analysis, birth attendants’ effect on the incidence of neonatal deaths was 5 times greater than mother’s age and parity.Keywords: Neonatal mortality, maternal age, parity, birth attendants